(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article is the result of a doctoral thesis in Education entitled Documentary Theatre: corners of experience, artistic action in praxis in basic education. It deals with the historical, political and artistic-pedagogical perspectives on Documentary Theater. The study proposes a teaching approach about reality, based on the concept of experience, and proves that Documentary Theater, when addressed in schools, can contribute to the negotiation and (re)creation of Culture by students. Among the results of the research, a curriculum based on non-fiction is born, which can be part of the methodologies chosen by the teacher. This approach reveals new possibilities for teaching theater and teaching in the context of the practices of the Pedagogy of Participation.